Selection of Digital Investment Instruments Applying the Multi-Objective Optimization by Ratio Analysis Method - Patria, Lintang; Marbun, Nasib; Sitompul, Bernad J. D.; Simangunsong, Pandi Barita Nauli (CV. Media Digital Publikasi Indonesia, 2023)
Choosing a digital investment instrument to make digital investments is not easy because behind the expected profits are also accompanied by balanced risks. Therefore, not a few novice investors are confused to determine the choice of digital investment instruments that are most appropriate for use in the long term. In this study the authors applied the decision support system method (Multi-Objective Optimization by Ratio Analysis) to facilitate the decision-making process in choosing digital investments for novice investors. The results of this study indicate that Alternative A4 (Trading) with a value of 0.17097 has the highest value compared to other alternatives, so Alternative A4 (Trading) is the most recommended digital investment instrument for use by novice investors.